Replication of obesity and diabetes-related SNP associations in individuals from Yucatán, México - Hernandez-Escalante, Victor M.; Nava-Gonzalez, Edna J.; Voruganti, V. Saroja; Kent, Jack W.; Haack, Karin; Laviada-Molina, Hugo A.; Molina-Segui, Fernanda; Gallegos-Cabriales, Esther C.; Lopez-Alvarenga, Juan Carlos; Cole, Shelley A.; Mezzles, Marguerite J.; Comuzzie, Anthony G.; et al. (Frontiers in Genetics, 2014)
The prevalence of type 2 diabetes (T2D) is rising rapidly and in Mexicans is approximately 19%. T2D is affected by both environmental and genetic factors. Although specific genes have been implicated in T2D risk few of these findings are confirmed in studies of Mexican subjects. Our aim was to replicate associations of 39 single nucleotide polymorphisms (SNPs) from 10 genes with T2D-related phenotypes in a community-based Mexican cohort. Unrelated individuals (n = 259) living in southeastern Mexico were enrolled in the study based at the University of Yucatan School of Medicine in Merida. Phenotypes measured included anthropometric measurements, circulating levels of adipose tissue endocrine factors (leptin, adiponectin, pro-inflammatory cytokines), and insulin, glucose, and blood pressure. Association analyses were conducted by measured genotype analysis implemented in SOLAR, adapted for unrelated individuals. SNP Minor allele frequencies ranged from 2.2 to 48.6 %. Nominal associations were found for CNR1, SLC30A8, GCK and PCSK1 SNPs with systolic blood pressure, insulin and glucose, and for CNR1, SLC30A8, KCNJ11 and PCSK1 SNPs with adiponectin and leptin (p < 0.05). P values greater than 0.0014 were considered significant. Association of SNPs rs10485170 of CNR1 and rs5215 of KCNJ11 with adiponectin and leptin, respectively, reached near significance (p = 0.002). Significant association (p = 0.001) was observed between plasma leptin and rs5219 of KCNJ11.